2015
DOI: 10.1159/000371679
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Obesity, Gut Microbiome and Hepatocellular Carcinoma Development

Abstract: During the past several decades, the percentage of excess bodyweight and obese adults and children has increased dramatically, and is becoming one of the most serious public health problems worldwide. Extensive epidemiological studies have revealed that there is a strong link between obesity and some common cancers. However, the exact molecular mechanisms linking obesity and cancer are not fully understood yet. Recently, we have reported that dietary or genetic obesity provokes alterations of gut microbiota pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 53 publications
(82 reference statements)
0
20
0
1
Order By: Relevance
“…Few studies have reported the direct effect of primary bile acids on intestinal carcinogenesis. 53,58,[62][63][64][65] In addition, DCA-mediated gut dysbiosis has a crucial role in the progression of the intestinal adenoma-adenocarcinoma sequence. 59 In HCT116 colon cancer cells, CDCA could increase COX-2 promoter activity, which was an important marker in carcinogenesis.…”
Section: Influence Of Gut Microbiota On Bile Acidsmentioning
confidence: 99%
“…Few studies have reported the direct effect of primary bile acids on intestinal carcinogenesis. 53,58,[62][63][64][65] In addition, DCA-mediated gut dysbiosis has a crucial role in the progression of the intestinal adenoma-adenocarcinoma sequence. 59 In HCT116 colon cancer cells, CDCA could increase COX-2 promoter activity, which was an important marker in carcinogenesis.…”
Section: Influence Of Gut Microbiota On Bile Acidsmentioning
confidence: 99%
“…Studies in animal models (murine) have shown that the enterohepatic circulation of dichloroacetic acid (DCA) provokes DNA damage and consequent cellular senescence in hepatic stellate cells which, in turn, secrete various inflammatory and tumour-promoting factors in the liver, thus facilitating HCC (Elinav et al, 2013;Hara, 2015;Ohtani, 2015). Another mechanism suggested is the conversion of ethanol into toxic and carcinogenic acetaldehyde by anaerobic bacteria in the colon.…”
Section: Hepatocellular Carcinoma (Hcc)mentioning
confidence: 99%
“…Although the exact molecular pathogenesis of HCC development in these viral liver diseases have not been fully revealed, tremendous progresses have been made in terms of clinical features, managements, oncogenic potential of viral proteins, and the critical role of viral genomic integration into the host genomes, as well as positive correlations between success of anti-viral therapy and decrease in HCC incidence [23–27]. In contrast, basic and clinical studies of NASH-HCC are in their infancy [17], and many clinical issues and basic understanding of NASH-HCC pathogenesis remain unexplored and elusive.…”
Section: Challenges In Investigating Nash-hccmentioning
confidence: 99%
“…One unsolved question remains whether cancer stem cells or tumor-initiating cells arise from transformation of normal tissue stem cells, or from dedifferentiation of mature hepatocytes or progenitor cells during steatohepatitis [90]. Other intriguing unsolved issues include, but are not limited to: 1) The impact of altered gut microbiome on bile acid metabolism and hepatic inflammation, steatosis and carcinogenesis [17]; 2) What is the epigenetic influence from aberrant adipokines, lymphokines, cytokines or transcription factors on normal stem cells, progenitor cells or mature hepatocytes [30, 90]; 3) Are there differences in energy and nutrient metabolism and the metabolomics profile between SFL, NASH and NASH-HCC; and 4) The molecular links between disordered lipid metabolism, ER stress, and insulin resistance and carcinogenesis [91]. Hopefully, reliable NASH-HCC models will be available in the near future which will enable these studies to be undertaken, and also be used to assess the effectiveness of potential therapeutics in the treatment of NASH and the prevention of HCC [46, 51].…”
Section: Prospective and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation